OP19 Classifying perianal fistulising Crohn's Disease: An expert-consensus to guide decision-making in daily practice and clinical trials. (21st January 2022) - Geldof, J; Iqbal, N; LeBlanc, J F; Sawyer, R; Buskens, C; Bemelman, W; Gecse, K; Lundby, L; Lightner, A L; Danese, S; Spinelli, A; Carvello, M; et al.
Abstract: Background: Perianal fistulising Crohn's disease (CD) is an aggressive disease phenotype that can have a significant impact on patients' quality of life. Current biological understanding of perianal fistulising CD remains inadequate and previous classification systems have not provided clear guidance on therapy in clinical practice nor on defining patient cohorts within clinical trials. To counter this unmet need, we propose a new classification system for perianal fistulising CD. Methods: The proposed classification system was developed through a modified nominal group technique expert consensus process involving open discussion and formal voting on previously defined statements. Consensus agreement was defined a priori as 80% voting "strongly agree" or "agree with minor reservation". Participants included gastroenterologists, radiologists, surgeons active in a tertiary IBD centre and a patient representative. Results: The classification identifies four groups of patients with perianal fistulising CD. Key elements include stratification according to disease severity as well as disease outcome; synchronisation of patient and clinician goals in decision making, with a proactive, combined medical and surgical approach, on a 'treat to patient goal' basis; and identification of indications for curative fistula treatment, diverting ostomy and proctectomy. The new classification retains an element of flexibility, in which patients can cycle through different classes over time. Furthermore, with each specific class comes a paired treatment strategy suggestion and description of clinical trial suitability. Conclusion: The proposed classification system is the first of its kind and is an important step towards tailored standardisation of clinical practice and research in patients with perianal fistulising CD.